Social vulnerability: A systematic review - Fernández-Cediel, Miryam C.; Loots, Gerrit; Villanueva, O’Driscoll (Notas de Antropología de las Américas, 2025)
Social vulnerability is a topic of concern in many territories of the world. We conducted a systematic review in the international context, contributing to social vulnerability knowledge. This review examined the different approaches from various disciplines that might help understand the use of this concept. It was found that social vulnerability must be understood in terms of exposure and sensitivity to risk and resilience. In turn, these elements are also related to sociodemographic characteristics, poverty, economic issues, health conditions, local security, social networks, and education. All these relationships are directly influenced by the policies and institutions that address or disregard all the elements that play an important role in social vulnerability.